Effect of study habits, information accessibility and use on learning outcomes of postgraduate students in University of Ibadan, Nigeria (2004)
This study examined effects of study habits, information accessibility and use on learning outcomes of postgraduate students in University of Ibadan, Nigeria. There were 64 males and 36 females in the sample. Out of this, 23 women and 39 men were married. Subjects responded to questions on information accessibility/use, study habits and learning outcomes. It was hypothesised and found from the Analysis of Variance (ANOVA) and mean that there is significant difference between information use and study habits based on sex. Likewise, information accessibility has influence on the study habits of University of Ibadan postgraduate students. Finally, it was found that study habits, information accessibility/use and learning outcomes revealed significant différences based on marital status of the respondents. The paper concluded that the respondents,are affected differently by timing, stress-coping ability, previous expérience and background knowledge of their discipline cum détermination to succeed.